Impressions of Life and Law on the High Court Bench - Palmer, Matthew SR (Victoria University of Wellington Law Review, 2018)
The following is a public lecture given at Victoria University of Wellington on 27 March 2018, organised by the New Zealand Centre for Public Law. In it Justice Matthew Palmer compares his impressions of life and law on the High Court Bench with that in practice and in academia.